The Role and Challenges in Preparing AMDAL Documents as an Effort to Prevent Environmental Pollution and Damage - Adam lutfi Aldian; Firza Ikhsan Mediansyah; Agus Irpan Nurhidayat; Cahya Darmawan (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2026)
The Environmental Impact Analysis (EIA) document is a crucial instrument in efforts to prevent pollution and environmental damage. It serves to identify, predict, and evaluate the potential impacts of a business plan or activity. This research uses a qualitative approach using literature review techniques to analyze the role of the EIA as a basis for decision-making and a monitoring instrument through the preparation of an Environmental Management Plan (RKL) and an Environmental Monitoring Plan (RPL). Furthermore, this research examines the role of the community and government agencies in ensuring the effective implementation of the EIA. The study results indicate that the EIA plays a strategic role in maintaining environmental sustainability through preventive measures and regular monitoring. However, its implementation still faces various obstacles such as poor document quality, minimal business awareness, weak oversight, and limited public participation. These findings emphasize the importance of strengthening regulations, increasing the capacity of supervisory institutions, and public involvement to achieve responsible and sustainable environmental management.